Current insights on the effects of medicinal plants in the management of obesity and infectious diseases: An update from 2020 - Ezichi Favour Ofoezie; Chinwendu Angela Ogbonna; Ezinne Tiffany George; Chioma Juliet Anunobi; Sandra C. Olisakwe; Simeon Babarinde; Chidera Godson Chukwuemeka; Uzochukwu Eric Ogbonna; Chibuzo Collette Amafili; Justina Onyinyechi Omaba; Henry Nnaemeka Ogbonna (Aspects of Molecular Medicine)
Medicinal plants have long played a pivotal role in traditional medicine, and their integration into modern healthcare is gaining recognition for their potential in treating a range of conditions, including obesity and infectious diseases. Their bioactive compounds offer a natural, sustainable alternative to synthetic drugs, with significant therapeutic benefits. This review focuses on the recent advances of medicinal plants in addressing two major global health challenges: obesity and infectious diseases. In modern medicine, these plants are valued for their ability to manage weight by influencing metabolic processes such as fat oxidation, insulin sensitivity, and inflammation. Additionally, their antimicrobial properties offer effective solutions against drug-resistant pathogens, presenting a complementary approach to conventional treatments. Through a comprehensive analysis of bioactive compounds, the review investigates their mechanisms, including enzyme inhibition, modulation of immune response, and disruption of microbial growth and biofilm formation. Key findings indicate that these phytochemicals demonstrate both anti-obesity and antimicrobial activities, with potential to reduce inflammation, improve metabolic health, and combat drug-resistant infections. In essence, medicinal plants hold significant promise as natural therapeutic agents for managing obesity and infectious diseases. Their ability to target multiple biological pathways simultaneously makes them effective in addressing the complex interplay between metabolic disorders and immune dysfunction.